2018
DOI: 10.1080/08923973.2018.1490319
|View full text |Cite
|
Sign up to set email alerts
|

A new sight for paraquat poisoning from immunology

Abstract: Paraquat (methyl viologen, PQ) is highly toxic to humans. Pulmonary fibrosis is the most common cause of death after PQ poisoning. However, no effective therapy is available. The current treatment dilemma and pathology suggest that we should reconsider how to treat the poisoning using other methods, such as immunization. Some clues indicate that immune mechanisms may play important roles in the pathology of PQ poisoning. We implemented a simple experiment to test the hypothesis that activated innate immunity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…PQ causes damage to multiple organs, i.e. lung, liver and kidney by disrupting various biological functions (Dinis-Oliveira et al 2008;Wu et al 2018). PQ toxicity has a high mortality rate, nevertheless no speci c medical therapy is available for it (Sun and Chen 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PQ causes damage to multiple organs, i.e. lung, liver and kidney by disrupting various biological functions (Dinis-Oliveira et al 2008;Wu et al 2018). PQ toxicity has a high mortality rate, nevertheless no speci c medical therapy is available for it (Sun and Chen 2016).…”
Section: Introductionmentioning
confidence: 99%
“…PQ toxicity has a high mortality rate, nevertheless no speci c medical therapy is available for it (Sun and Chen 2016). Tissue injury is mainly due to reactive oxygen species (ROS) causing irreversible oxidative damage to molecular structures, cell functions and exacerbated immune response (Wu et al, 2018). Recent studies have shown that PQ directly impacts on immunity and immune cell activities (Hassuneh et al 2012;Riahi et al 2010) with effects such as decreased interferon (IFN)-γ production and phagocytic activity of monocytes in mice (Riahi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Paraquat-induced lung injury pathophysiologically manifests as reduced pulmonary ventilation, reduced lung compliance, and ventilation/perfusion defects[ 21 ]. In the early stage, lung CT shows no abnormality or only an increase of lung markings and mild ground-glass-like changes.…”
Section: Discussionmentioning
confidence: 99%
“…Paraquat (PQ) is a highly toxic non-selective herbicide that is widely used throughout the world. PQ is known to causes damage to numerous organs including the lung, brain, kidney, heart, liver, and immune system [1,2,3]. Thus, the toxicities of PQ have been broadly investigated [1].…”
Section: Introductionmentioning
confidence: 99%
“…Although the immunotoxicities of PQ are complex, PQ is a confirmed toxicant to both innate and adaptive immune system [3]. For instance, PQ impaired cytotoxic capacity of nature killer (NK) cells via induction of metallothionein in mice [4].…”
Section: Introductionmentioning
confidence: 99%